EKSTRAKSI SENYAWA BIOAKTIF THEAFLAVIN TEH OOLONG (CAMELLIA SINESIS) DENGAN AIR SEBAGAI GREEN SOLVENT - Amalia, Rizka; Yulianto, Mohamad Endy; Purwantisari, Susiana; Yudanto, Yusuf Arya; Pangestu, Ilyas Teguh (Vocational School Diponegoro University, 2020)
Theaflavin, a polyphenolic compounds foundÂ in oolong tea and black tea, thought to have medicinal potency. Theaflavins and their derivatives such as theaflavin gallate have shown a broad spectrum of antiviral activity against several viruses, including influenza A, B and hepatitis C viruses. Previous research show that theaflavins could inhibit RdRp activity through blocking the active site in the catalytic pocket ofÂ RdRpÂ in SARSâ€CoVâ€2, SARSâ€CoV and MERSâ€CoV.. This research aims to extract theaflavins in oolong tea with water solvent at a temperature of 100oC, pressure > 1 atm and varied extraction times (10-60 minutes). The effect of oolong tea extraction time towards theÂ theaflavin content was observed. The results showed that with the longer extraction time, the theaflavin levels were reduced due to the degradation of thermal theaflavins into thearubigins. The model exponential equation obtained is Â y=14,91488 e-0,2631x + 0,11865, with the R2=0.99161. The best operating conditions was obtained at 10 minutes of extraction time, resulted in 1.19% of the total theaflavin content of oolong tea.